EXPERIMENTAL TESTING OF THE 4K EDUCATIONAL TECHNOLOGY (COMMUNICATION, COLLABORATION, CRITICAL THINKING, CREATIVITY) IN PRIMARY SCHOOL SETTINGS (International journal of artificial intelligence, 2026)
This study investigates the experimental implementation of the 4K educational technology—comprising Communication, Collaboration, Critical Thinking, and Creativity—within primary school classrooms. As modern pedagogical paradigms shift from rote memorization to skill-based learning, the early integration of 21st-century skills becomes paramount. Through a controlled pedagogical experiment involving primary school students, this research measures the cognitive and social development impacts of the 4K framework compared to traditional teaching methods. The findings reveal significant improvements in students' collaborative problem-solving abilities and creative output, suggesting that embedding 4K methodologies early in the educational trajectory profoundly enhances holistic student development.